EU competition policy, vertical restraints, and innovation: an analysis from an evolutionary perspective - Wolfgang Kerber; Simonetta Vezzoso (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
The EU competition policy in regard to vertical restraints is mainly based upon neoclassical efficiency-oriented reasonings, leading to a neglect of the innovation dimension. This paper analyses to what extent evolutionary theories of competition and innovation economics can be used to derive additional, new criteria for the assessment of vertical restraints. It is shown that Neo- Schumpeterian and Hayekian approaches to competition and innovation economics as well as knowledge-based theories of the firm are capable to provide a basis for a different framework for analysing the impact of vertical agreements. Specific evolutionary arguments, such as subjective and local knowledge, the heterogeneity of knowledge bases of firms, communication and learning problems, and the complementarity of knowledge (systemic innovations) can be used for deriving additional, new assessment criteria for vertical restraints. The analysis is made against the background of the most recent reforms of EU competition rules in regard to vertical restraints. It also shows how evolutionary approaches to competition and innovation might be used for competition policy.
Keywords: K21; L42; B52; 330; European competition policy; vertical restraints; evolutionary economics; innovation economics; Wettbewerbspolitik; EU-Politik; Vertikale Konzentration; Wettbewerbsbeschränkung; Innovation; Evolutionsökonomik; EU-Staaten